Introducing Precipitated Calcium Carbonate (PCC) as a white rubber filler - Supranto, Supranto (2009)
It have been known to add a layered mineral filler to a rubber to mix them in order to improve gas-barrier properties of the rubber . The layered mineral filler in the form of flat is not permeable to gas, and therefore it is generally considered that the gas-barrier properties of the rubber composition can be improved by the volume fraction of the filler mixed with the rubber . Examples of the layered mineral filler used include clay, mica and talc. Preferred are clay, mica and talc because they have flat shape. The mean particle size of the layered mineral filler is generally not more than 20 μm, preferably 0.1 to 15 μm, especially 0.1 to 8 μm. Precipitated calcium carbonates (PCC) has found use in a broad range of manufactured and consumer products ranging from paper and paper coatings to plastic and elastomer reinforcement to food supplements and cosmetics. Calcium carbonate is particularly useful in paper coatings, because it is relatively inexpensive and imparts good optical performance characteristics to paper resulting in a brighter, glossier more opaque paper, while also providing a high resistance to yellowing and aging. PCC is a desirable form of the material because it has a platy structure that is especially good at imparting desirable functional properties such as high gloss, whiteness and opacity when prepared as part of a paper coating. PCC has a mean particle size smaller than that of clay, mica and talc. Therefore PCC may be used as white rubber filler substituting the clay, mica and talc. This paper presented the result of preliminary research on introducing PCC as a white rubber filler.